Aromaticity and Other Conjugation Effects. By Rolf Gleiter and Gebhard Haberhauer. Issue 9 (30th January 2013) - Scott, Lawrence T.; Cho, Hee Yeon; Eliseeva, Maria N.; Jackson, Edward A.; Tanaka, Takayuki; Tanikawa, Tomoharu
<x xml:space="preserve">Abstract</x> Wiley‐VCH, Weinheim, 2012. 452 pp., hardcover, € 129.00.—ISBN 978‐3527329465 (softcover, € 59.00.—ISBN 978‐3527329342)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>